Pengaruh model hybrid learning dan minat belajar terhadap kreatifitas hasil belajar Bahasa Indonesia - Ernawati (Journal of Creative Attitudes Culture, 2023)
The purpose of this research is to test the hybrid learning model and interest in learning Indonesian language learning outcomes. This research uses a 2X2 factorial quasi-experimental design. Research data was collected using questionnaire methods and test methods. Then the data was analyzed using the two-way ANOVA statistical analysis technique. The research population was all class III students at SDN Ngelawak Kec. Prambon, Nganjuk Regency. In this research, the instruments used were questionnaires and Indonesian language learning results tests. This questionnaire uses a Likert scale. Data collection methods commonly used in research are tests, interviews, questionnaires and observation. Based on the research, the following results were obtained: (1) Learning Indonesian using a hybrid learning model produces better Indonesian language learning outcomes compared to online learning, (2) Students who have a high level of interest in learning produce better Indonesian language learning outcomes. compared to online learning. with students who have a low level of interest in learning, and (3) Learning Indonesian using a hybrid learning model for students who have a high level of interest in learning have better results in learning Indonesian than students who have a low level of interest in learning. Based on the research results, it was concluded that the use of the Hybrid Learning Model and interest in learning can improve Indonesian language learning outcomes